Design of resonator cavity for liquid material characterization - Nur Shahira Mat Hussain; Azahani Natasha Azman; Nurhafizah Abu Talip Yusof; Nur Alia Athirah Hj Mohtadzar; Mohamad Shaiful Abdul Karim (Universitas Ahmad Dahlan, 2022)
Dielectric characterization is very essential before the material can be utilized in designing microwave networks. Circular cylindrical resonators have been widely used for material characterization, but it is not a preferable design during the measurement of liquid samples as the sample placement requires repetitive process of opening and closing the lid of the cavity. This repetition procedure easily affects the accuracy of measurement and may lead to a measurement error. In this study, a rapid and less measurement procedure of liquid material characterization is proposed. The proposed rectangular resonator design is far more convenient and easier to handle as it does not require complex sample preparation. Considering electric field leakage, a hole is designed at the top of the cavity to ease the inserting process of sample. A 5-GHz prototype of a rectangular resonator is designed and fabricated to measure a liquid sample. Complex scattering parameters are measured using a vector network analyzer before the dielectric properties are estimated using an inverse technique. The dielectric properties of distilled water are measured to demonstrate the practicality of the proposed measurement technique. As a result, the measured dielectric properties of distilled water show a reasonable agreement with the values from other literature